Territories in contestation: relational power in Latin America - Clare, Nick; Habermehl, Victoria; Mason-Deese, Liz (Taylor & Francis, 2017)
Situated in geography’s recent territorial (re)turn, and drawing on Latin American theory and research, this paper examines the relational and contested nature of territories and territorial praxis. Engaging with contemporary literatures, we note the centrality of power to territory. However, as we explore in this paper, many analyses of power are too simplistic, with a latent attachment to sovereignty which can marginalise counter-hegemonic territorial politics. To combat this we explore two conceptions of power, as found in open and autonomist Marxism – poder (understood as power over) and potencia (understood as power to) – and how they function territorially. While such an understanding of power frames the complex production of territories, it is important to also reflect on how movements intervene in producing their own territories. Accordingly, the paper examines the territorial struggles of the Zapatistas, and, drawing from original research, explores how territorial ideas operate in everyday contexts in Buenos Aires, Argentina. Across these examples the paper illustrates the potential of ‘territories in resistance’, but also engages in how these are also contested. Led by our cases we emphasise the relational and contested construction of territory, ultimately developing a more nuanced understanding of territory and territorial praxis.